4.55 kW LD end-pumped Nd:YAG surface gain slab laser. (27th November 2018) - Liu, Yang; Lei, Jian; Li, Tianqi; Li, Ning; Tang, Xiaojun
Abstract: To improve the laser output power of a single module, we report on a master-oscillator Nd:YAG surface gain slab laser system with up to 4.55 kW of continuous-wave output power. The stable output power of the slab laser is achieved in the plane-parallel resonator with the 4f system. Image relaying along the slow axis is used to obtain the uniform distribution of pumping light in the slab width direction, and the methods of spatial multiplexing and polarization multiplexing are used to increase the density of pump power. The experimental results provided the basis of the optimization of high power slab lasers.